Highly Nonlinear Organic-Silicon Slot Waveguide for Ultrafast Multimode All-Optical Logic Operations - Yonghua Wang; Haofan Yang; Wenchan Dong; Lei Lei; Jing Xu; Xinliang Zhang; Ping Xu (IEEE Photonics Journal)
Highly nonlinear multimode optical integrated devices hold great promise for the emerging large-capacity mode division multiplexing (MDM) technology, and they correspondingly enable multimode optical signal processing at nodes of the MDM network. Here, we propose a highly nonlinear multimode organic-silicon slot waveguide (HN-OSSW) whose nonlinearity is greatly improved by the intensive optical field confinement in the nano-gaps filled with highly nonlinear organic material. Specifically, the achieved nonlinear coefficients of the HN-OSSW under TE0 and TE1 modes are estimated higher than 7000 W−1m−1 and 5800 W−1m−1, respectively. Also, by phase mismatch optimization, this nanostructure exhibits superior intramode four-wave mixing conversion efficiency but ignorable intermode crosstalk. Coupling efficiency of the mode multiplexer and the optimal nonlinear interaction length are discussed in detail. Based on the HN-OSSW, we then numerically demonstrate a multimode all-optical hexadecimal addition and subtraction for sixteen phase-shift keying (16PSK) signals with the operation rate of 1.28Tb/s. Six different logic operations including A+B-C, A+C-B, B+C-A, A+B, A-B and B-A are simultaneously obtained with good performance evaluations, indicating the promising prospect of the HN-OSSW applied in ultrafast multimode signal processing.